An evaluation of the appropriateness of advice and healthcare contacts made following calls to NHS Direct Wales - Rance Jaynie; Cheung Wai-Yee; Munro James; Peconi Julie; Snooks Helen; Williams Anne (BMC, 2009)
Abstract Background An evaluation of NHS Direct Wales (NHSDW), a national telephone-based healthcare advice and information service, was undertaken. A key objective was to describe the actions of callers and assess the appropriateness of advice and healthcare contacts made following calls, results of which are reported here. Methods Postal questionnaires were sent to consecutive callers to NHSDW in May 2002 and February 2004 to determine 1) callers' actions following calls and 2) their views about the appropriateness of: advice given; and when to seek further care. An independent clinical panel agreed and applied a set of rules about healthcare sites where examinations, investigations, treatments and referrals could be obtained. The rules were then applied to the subsequent contacts to healthcare services reported by respondents and actions were classified in terms of whether they had been necessary and sufficient for the care received. Results Response rates were similar in each survey: 1033/1897 (54.5%); 606/1204 (50.3%), with 75% reporting contacting NHSDW. In both surveys, nearly half of all callers reported making no further healthcare contact after their call to NHSDW. The most frequent subsequent contacts made were with GPs. More than four fifths of callers rated the advice given - concerning any further care needed and when to seek it - as appropriate (further care needed: survey 1: 673/729, 82.3%; survey 2: 389/421, 92.4%; when to seek further care - survey 1: 462/555, 83.2%; survey 2: n = 295/346, 85.3%). A similar proportion of cases was also rated through the rule set and backed up by the clinical panel as having taken necessary and sufficient actions following their calls to NHSDW (survey 1: 624/729, 80.6%; survey 2: 362/421, 84.4%), with more unnecessary than insufficient actions identified at each survey (survey 1: unnecessary 132/729, 17.1% versus insufficient 11/729, 1.4%; survey 2: unnecessary 47/421, 11.0% versus insufficient 14/421, 3.3%). Conclusion Based on NHSDW caller surveys responses and applying a transparent rule set to caller actions a large majority of subsequent actions were assessed as appropriate, with insufficient contacts particularly infrequent. The challenge for NHSDW is to reduce the number of unnecessary contacts made following calls to the service, whilst maintaining safety.